Influence of N-acetyl-5-methoxytryptamine on Fetal Lung Maturation in Experimental Preterm Delivery Model - Celik, Onder; Hascalik, Seyma; Tamser, Mustafa; Kirimliolu, Hale; Guven, M. Atahan; Dogru, M. Ilker; Yurekli, Muhittin (Galenos Yayincilik, 2007)
Objective: The study was planned to investigate the effect of pharmacological concentrations of melatonin on maturation of the fetal lung in preterm delivered rats. Materials and Methods: Thirty pregnant rats were divided into three groups. The study group received either betametasone (n=10) or melatonin (n=10) between 17th and 18th days of gestation, whereas the third group (n=10) served as control. Pregnancies were terminated on the 21st days of gestation in the control group and on the 19th days of gestation in the betametasone and melatonin groups. Amniotic fluid adrenomedullin, nitric oxide (NO) concentrations and lamellar body count were determined and results compared with each other. Results: The adrenomedullin levels of the melatonin, betametasone and control groups were found to be 29.84 +/- 3.45 pg/ml, 43.15 +/- 6.63 pg/ml and 49.39 +/- 12.93 pg/ml, respectively. The mean lamellar body count was found to be five fold higher in the control group than that in the melatonin group; and, it was 4.1 fold higher in the betametasone group than that in the melatonin group. There were no significant difference among the groups regarding the NO levels. Lamellar body counts of the betametasone and control groups were higher than those which have received melatonin, but the difference was not statistically significant (p>0.05). Masson's trichrome stained section were similar in all groups. Discussion: Melatonin was found to maintain the 19th day amniotic fluid adrenomedullin, lamellar body and NO levels within the 21st day limits. It is possible that adrenomedullin secretion was modulated by exogenous melatonin administration and melatonin may have been involved in the regulation of fetal lung maturation.
Keywords: fetal lung maturation; melatonin; betametasone; adrenomedullin; NO; lamellar body